2021
DOI: 10.3390/clinpract11030062
|View full text |Cite
|
Sign up to set email alerts
|

Fluoropyrimidine-Induced Severe Toxicities Associated with Rare DPYD Polymorphisms: Case Series from Saudi Arabia and a Review of the Literature

Abstract: Dihydropyrimidine dehydrogenase (DPD) is the major enzyme in the catabolism of 5-Fluorouracil (5-FU) and its prodrug capecitabine. We report cases from our institute with colorectal cancer who experienced severe toxicities to standard dose 5-FU based chemotherapy. DPYD gene sequencing revealed rare different polymorphisms that prompted dose adjustments of administered 5-FU and capecitabine. To our knowledge, this is the first case series looking at DPYD polymorphisms in the Saudi Arabian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…13 DPYD variants (1 splice donor, 8 missense, 4 intronic) were reported in patients of Middle Eastern ancestry. There were 2 cohort studies from Tunisia 79,80 , 1 cohort study from Jordan 81 1 case report from Lebanon 82 and 1 case series from Saudi Arabia 83 (Supplementary Table 5). None of the variants passed our filtering process (Supplementary Results).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 DPYD variants (1 splice donor, 8 missense, 4 intronic) were reported in patients of Middle Eastern ancestry. There were 2 cohort studies from Tunisia 79,80 , 1 cohort study from Jordan 81 1 case report from Lebanon 82 and 1 case series from Saudi Arabia 83 (Supplementary Table 5). None of the variants passed our filtering process (Supplementary Results).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, there are other variants in these ethnic groups which need further investigation. For example, in South Asians and Middle Easterners, our systematic review identified single occurrence of missense variants c.704G>A (p.Arg235Gln, rs755416212) 90 and c.257C>T (p.Pro86Leu, rs568132506) 83 , respectively. These variants are not reported in the CPIC guideline but are predicted to be deleterious by >80% of the in silico tools we used, with one research study reporting significant reduction of DPD activity in vitro with the c.257C>T variant 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, there are other variants in these ethnic groups which need further investigation. For example, in South Asians and Middle Easterners, our systematic review identified single occurrence of missense variants c.704G>A (p.Arg235Gln, rs755416212) [91] and c.257C>T (p.Pro86Leu, rs568132506) [84], respectively. These variants are not reported in the CPIC guideline but are predicted to be deleterious by 100% of the in silico tools we used, with one research study reporting significant reduction of DPD activity in vitro (97% decrease) with the c.257C>T variant [42].…”
Section: Discussionmentioning
confidence: 99%
“…13 DPYD variants (1 splice donor, 8 missense, 4 intronic) were reported in patients of Middle Eastern ancestry. There were 2 cohort studies from Tunisia [80,81], 1 cohort study from Jordan [82], 1 case report from Lebanon [83], and 1 case series from Saudi Arabia [84] (Supplementary Table 5). None of the variants passed our filtering process (Supplementary Results).…”
Section: Dpyd Genetic Variants Haplotypes and In Silico Predictionsmentioning
confidence: 99%
“…DPD metabolizes over 80% of 5-FU in the liver. The conversion of 5-FU to inactive dihydrofluorouracil (DHFU) occurs through the DPD enzyme [6][7][8]. TYMS is the enzyme that converts deoxyuridine monophosphate (dUMP) to deoxythymidine monophosphate (dTMP), which is critical for DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%